Predation on northern shrimp (Pandalus borealis) by three gadoid species. Issue 4 (21st April 2017) - Jónsdóttir, Ingibjörg G.
ABSTRACT: Northern shrimp ( Pandalus borealis ) is targeted by commercial fisheries, but is also an important prey in the marine food web. In this study, stomach content data were used to study predation on shrimp by three gadoid species, cod ( Gadus morhua ), haddock ( Melanogrammus aeglefinus ) and whiting ( Merlangius merlangus ), in six inshore areas around Iceland. The results showed that shrimp was more important in the diet of cod compared with the other two predators. However, the overall predation pressure was similar for cod and haddock due to the high abundance of haddock. Therefore, even though shrimp is not the primary source of food for haddock, this species can have a substantial effect on shrimp stocks when haddock abundance is high. In addition, while cod and haddock did not select for any particular size of shrimp, whiting seemed to preferentially target juvenile shrimp. The results suggest that due to the overall effects of these three predators on shrimp stocks, gadoids need to be included in the management of shrimp stocks as predation is one of the major drivers in the development of this important prey stock.